Modelling Considerations in the Simulation of Hydrogen Dispersion within Tunnel Structures. (13th May 2012) - Ismail, Idris; Tsukikawa, Hisayoshi; Kanayama, Hiroshi
Abstract : The flow of leaked hydrogen gas in tunnel structures is simulated through a free, open source computational fluid dynamics (CFD) code for incompressible thermal convection flow. A one-fifth scale experimental model of a real tunnel is the target model to be simulated. To achieve this, studies on the effects of different boundary conditions, in particular, the wind speed, are carried out on smaller tunnel structures with the same hydrogen inlet boundary conditions. The results suggest a threshold/limiting value of air speed through tunnel. The target model computed with the most suitable boundary conditions shows some agreement with the experimental ones. A method to compute the buoyancy factor used in the code is also presented.